The Effectiveness of Presentation Practice Production (PPP) Model in Teaching Speaking to 8th Graders - Shofiroh, Nadziyah; Noviyanti, Masyitah (Nusantara Educational Review, 2024)
This study uses a descriptive qualitative method, using observation and interview instruments. The results of the data analysis show that the implementation of the Presentation, Practice, Production (PPP) model has three stages. Each phase has different roles, activities, and models, in the presentation phase, the teacher introduces new language to students, done by using pictures or reading text. In the practice phase, students practice the new language in the control language. In the production phase, students are encouraged to use the new language in a freer way with communication tasks or creating paragraphs. The use of recount texts in learning is very useful, especially for training students' speaking skills. Although some students have difficulty in pronunciation, the Presentation, Practice, Production (PPP) model helps them be motivated to speak with teacher guidance, so that they can speak English better gradually. Penelitian ini menggunakan metode deskriptif kualitatif dengan menggunakan instrumen observasi dan wawancara. Hasil dari analisis data menunjukkan bahwa implementasi model Presentation, Practice, Production (PPP) ada tiga tahap. Setiap fase memiliki peran, aktivitas, dan model yang berbeda, dalam fase presentasi, guru memperkenalkan bahasa baru kepada siswa, dilakukan dengan menggunakan gambar atau membaca teks. Pada fase latihan, siswa mempraktikkan bahasa baru dalam bahasa kontrol. Pada tahap produksi, siswa didorong untuk menggunakan bahasa baru dengan cara yang lebih bebas dilakukan dengan tugas komunikasi atau membuat paragraf. Penggunaan teks recount dalam pembelajaran sangat bermanfaat, terutama untuk melatih kemampuan berbicara siswa. Meskipun beberapa siswa kesulitan dalam pengucapan, model Presentation, Practice, Production (PPP) membantu mereka termotivasi berbicara dengan bimbingan guru, sehingga mereka dapat berbicara bahasa Inggris dengan lebih baik secara bertahap.